Training Creation Teaching Modules Merdeka Curriculum to Improve The Quality of Physical Education Sports and Health Teachers - Arief Darmawan; Zihan Novita Sari; Surya Adi Saputra; Ahadi Priyohutomo; Cahyo Nugroho Sigit (GANDRUNG: Jurnal Pengabdian Kepada Masyarakat, 2025)
Merdeka Curriculum emphasizes the importance of the role of teachers as facilitators who are able to manage teaching modules to maximize student potential. In this context, training for teachers, especially physical education teachers, is needed so that they can design relevant and effective modules, while also overcoming challenges in their implementation. Methods used in this service are the lecture method, mentoring, and measurement of results. Results of this service show that this training has an important role in improving the competence of PJOK teachers in implementing the independent curriculum effectively. Through the presentation of basic principles, introduction of important components of teaching modules, and direct practice through group discussions and presentations, teachers gain a deeper understanding of the flexibility and application of the independent curriculum in learning. This training not only helps teachers understand the technical aspects of compiling teaching modules, but also encourages collaboration and sharing of experiences between participants, which contributes to increasing creativity and adaptation of learning methods.